Night of the assassins : the untold story of Hitler's plot to kill FDR, Churchill, and Stalin - Blum, Howard (Harper, an imprint of HarperCollinsPublishers, 2020)
The mission: to kill the three most important and heavily guarded men in the world. The assassins: a specially trained team headed by the killer known as The Most Dangerous Man in Europe. The stakes: nothing less than the future of the Western world. The year is 1943 and the three Allied leaders<U+2014>Franklin D. Roosevelt, Winston Churchill, and Joseph Stalin<U+2014>are meeting for the first time at a top-secret conference in Tehran. But the Nazis have learned about the meeting and Hitler sees it as his last chance to turn the tide. Although the war is undoubtedly lost, the Germans believe that perhaps a new set of Allied leaders might be willing to make a more reasonable peace in its aftermath. And so a plan is devised<U+2014>code name Operation Long Jump<U+2014>to assassinate FDR, Churchill, and Stalin. Immediately, a highly trained, hand-picked team of Nazi commandos is assembled, trained, armed with special weapons, and parachuted into Iran. They have six days to complete the daring assignment before the statesmen will return home. With no margin for error and little time to spare, Mike Reilly, the head of FDR<U+2019>s Secret Service detail<U+2014>a man from a Montana silver mining town who describes himself as “an Irish cop with more muscle than brains”<U+2014>must overcome his suspicions and instincts to work with a Soviet agent from the NKVD (the precursor to the KGB) to save the three most powerful men in the world. Filled with eight pages of black-and-white photographs, Night of the Assassins is a suspenseful true-life tale about an impossible mission, a ticking clock, and one man who stepped up to the challenge and prevented a world catastrophe.